2019
DOI: 10.3389/fnagi.2019.00147
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Brain Regions in Physiological and Pathological Brain Aging

Abstract: Background Studying structural brain aging is important to understand age-related pathologies, as well as to identify the early manifestations of the Alzheimer’s disease (AD) continuum. In this study, we investigated the long-term trajectory of physiological and pathological brain aging in a large number of participants ranging from the 50s to over 80 years of age. Objective To explore the distinct brain regions that distinguish pathological brain aging from physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Previous study showed inverse change of CTh and MD in early stage of AD [31]. Such regions of change in radiality were entorhinal cortex, parahippocampal gyrus, middle temporal gyrus, superior and middle frontal gyrus and the supramarginal gyrus bilaterally; a pattern which is similar to that seen in studies of cortical thickness [32]. That is, we could confirm that EMCI may predate LMCI in the perspective of disease progression.…”
Section: Discussionsupporting
confidence: 84%
“…Previous study showed inverse change of CTh and MD in early stage of AD [31]. Such regions of change in radiality were entorhinal cortex, parahippocampal gyrus, middle temporal gyrus, superior and middle frontal gyrus and the supramarginal gyrus bilaterally; a pattern which is similar to that seen in studies of cortical thickness [32]. That is, we could confirm that EMCI may predate LMCI in the perspective of disease progression.…”
Section: Discussionsupporting
confidence: 84%
“…Recent research demonstrated the importance of the hippocampus volumetric reduction as an indicator of AD (40). there is evidence that AD is associated with the hippocampus and superior and inferior lateral temporal regions (41). the importance of the precuneus and inferior temporal regions in pathological brain aging was proven previously (42).…”
Section: Discussionmentioning
confidence: 86%
“…However, cortical thickness declines even in physiological aging, such that the comparison of an elderly individual to that reference group will result in more pronounced atrophy detection, which would not necessarily have to be pathologic [10,15]. Nevertheless, given that the regions that exhibit cortical thinning differ in physiological and pathological aging (for example, atrophy of brain regions such as the precuneus and the inferior temporal region can be indicative of early signs of dementia [35]), it is still possible to detect such potential pathologic signatures using the method proposed here. This is possible because the reference system suggested herein was generated and evaluated for different brain regions separately.…”
Section: Discussionmentioning
confidence: 99%